MENINGKATKAN KOMPETENSI GURU MENYUSUN RPP 1 LEMBAR TERINTEGRASI DENGAN IN HOUSE TRAINING ( IHT) DI SMP NEGERI 4 MUARA BUNGO - Hasan, Hasan (Jurnal Pengabdian Pendidikan Masyarakat (JPPM), 2021)
The background of this research is from the existence of a policy for the preparation of RPP 1 Sheet initiated by the Minister of Education and Culture to help reduce the burden on teachers in the field of learning administration. This study aims to improve teacher competence to prepare RPP 1 sheet Integrated PPK, Literacy, HOTS and 21st Century Skills (4C) through In Hause Training (IHT) activities at SMP Negeri 4 Muara Bungo. The study used a School Action Research (PTS) design which consisted of planning, implementing, observing, and reflecting. This school action research was carried out in two cycles. The data obtained were processed qualitatively based on the percentage of achievement which was described descriptively based on the research cycle. Increasing teacher competence in preparing RPP 1 sheet integrated with In House Training (IHT) at SMP Negeri 4 Muara Bungo gave satisfactory results. The mentoring that was carried out for two cycles gave significant changes to the quality of the RPP produced. After mentoring activities, skilled teachers prepare lesson plans which contain 13 components in accordance with Permendikbud No. 22 of 2016 concerning process standards. In addition, teachers are skilled at compiling 1 sheet of RPP according to Minister of Education and Culture Circular No. 14 of 2019. The lesson plans made by the teacher have also integrated 21st century character, literacy, HOTS, and skills. Quantitatively, the results of the training in cycle II, the teacher's average score was 69.46 with a percentage of 86.8% with very good criteria. So this activity has a positive impact on teacher competence in preparing RPP 1 sheet integrated KDP, literacy, HOTS, and 21st century skills (4C).